Super-Resolution Arterial Spin Labeling Using Slice-Dithered Enhanced Resolution and Simultaneous Multi-Slice Acquisition - Shou, Qinyang; Shao, Xingfeng; Wang, Danny J. J. (Frontiers in Neuroscience, 2021)
Purpose: To achieve high spatial resolution (isotropic-2mm) perfusion imaging using 2D simultaneous multi-slice (SMS) pseudo-continuous arterial spin labeling (pCASL) and slice dithered enhanced resolution (SLIDER) technique for super-resolution reconstruction. Methods: The SLIDER-SMS pCASL with a multi-band factor of four was implemented at 3T with three numbers of slice shift (2/3/4) for the slice thickness of 4/6/8mm respectively. Super-resolution reconstruction was performed with singular value decomposition and different levels of Tikhonov regularizations. Temporal and spatial SNR as well as spatial blurring effect of super-resolution ASL images were measured in 5 healthy subjects and compared with those of reference high-resolution ASL images. Results: Compared to conventional 2D SMS ASL, super-resolution ASL images with isotropic-2mm resolution yielded 42%, 61% and 88% higher spatial SNR, and 18%, 55% and 105% higher temporal SNR with slice shift number of 2/3/4, respectively. Spatial blurring effect increased for SLIDER reconstruction from 2 to 4 slice shift. Conclusion: The proposed SLIDER-SMS pCASL technique can achieve whole-brain high-resolution perfusion images with ~15min scan time and improved SNR compared to standard 2D SMS pCASL. Caution needs to be exercised on quantifying and controlling blurring effects of SLIDER reconstruction.